Effect of Nigella sativa (black seed) supplementation on glycemic control: A systematic review and meta‐analysis of clinical trials. (14th March 2019) - Askari, Gholamreza; Rouhani, Mohammad Hossein; Ghaedi, Ehsan; Ghavami, Abed; Nouri, Mehran; Mohammadi, Hamed
Abstract : This study was aimed to quantify the antihyperglycemic effect of Nigella sativa ( N .  sativa ). An in‐depth search to identify clinical trials investigating the impact of N .  sativa on glycemic indices via MEDLINE, EMBASE, Scopus, Web of Science, Cochrane Library, and Google scholar databases were performed up to November 2018. We used a random effects model to estimate pooled effect size of fasting plasma glucose (FPG), postprandial blood glucose (PPBG), and hemoglobin A1c (HbA1c). A total of 17 randomized controlled trials investigating the effects of N .  sativa on FPG, PPBG, and HbA1c were included. Meta‐analysis suggested a significant association between N .  sativa supplementation and reduction in FPG (weighted mean difference [WMD]: −9.93 mg/dl, 95% CI [−13.44, −6.41]), PPBG (WMD: −14.79 mg/dl, 95% CI [−24.19, −5.39]), and HbA1c (WMD: −0.57%, 95% CI [−0.77, −0.37]). Subgroup analysis revealed that N .  sativa oil was more effective than N .  sativa powder in reduction of FPG. To sum up, N .  sativa consumption has a significant lowering effect on glycemic status. Further studies with prolonged durations and powerful design are needed to specify the exact mechanism, optimal dosage, and duration of N .  sativa supplementation to obtain a beneficial effect on glycemic status.